(untitled) (Huellas, 2016)
The concept of food sovereignty arises today as a political challenge to the concept of food safety, which is a notion associated with the dominant model of agriculture and feeding. In the early 1990s a number of alternative social movements were organized into the transnational agrarian movement La Vía Campesina. They argued that the current crisis is the result of the globalization of an agriculture neoliberal model of capital intensive and industrial characteristics. The transformation of the rural areas and the worldwide urbanization process pose important challenges with respect to food sovereignty. This article aims at analyzing the role of city farming in relation to key elements of food sovereignty around the concept of proximity. The study was conducted on the metropolitan area Santa Rosa-Toay located in the Argentinian pampas. The methodological design was based on a blended approach. Questionnaires and field surveys were conducted, Google Earth was used as a mapping tool, and free software was used for processing information through GIS. The results obtained include the production of thematic maps and the conceptual deepening on the scope of the concept of proximity agriculture.